2009
DOI: 10.1097/md.0b013e3181b8fccb
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Diseases Consultation Lowers Mortality From Staphylococcus aureus Bacteremia

Abstract: Staphylococcus aureus bacteremia (SAB) is a lethal and increasingly common infection in hospitalized patients. We assessed the impact of infectious diseases consultation (IDC) on clinical management and hospital mortality of SAB in 240 hospitalized patients in a retrospective cohort study. Patients who received IDC were older than those who did not (57.9 vs. 51.7 yr; p = 0.05), and were more likely to have a health care-associated infection (63% vs. 45%; p < 0.01). In patients who received IDC, there was a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(78 citation statements)
references
References 20 publications
2
72
1
3
Order By: Relevance
“…Anecdotally, infectious-disease physicians were more likely to respond to the PCR assay, suggesting that physicians who were more familiar with molecular diagnostic tests were more likely to use the result to guide antibiotic therapy decisions. In our view, the effect of infectious-disease consultation should not be underestimated: in previous studies, involvement of infectious-disease physicians was associated with reduced mortality in patients with S. aureus bacteremia in the absence of rapid diagnosis (6,10). Furthermore, Forrest et al have reported outcome improvements for patients with S. aureus bacteremia from the use of a rapid fluorescence in situ hybridization (FISH) test (peptide nucleic acid [PNA]-FISH) that distinguished S. aureus from coagulase-negative staphylococci (4).…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotally, infectious-disease physicians were more likely to respond to the PCR assay, suggesting that physicians who were more familiar with molecular diagnostic tests were more likely to use the result to guide antibiotic therapy decisions. In our view, the effect of infectious-disease consultation should not be underestimated: in previous studies, involvement of infectious-disease physicians was associated with reduced mortality in patients with S. aureus bacteremia in the absence of rapid diagnosis (6,10). Furthermore, Forrest et al have reported outcome improvements for patients with S. aureus bacteremia from the use of a rapid fluorescence in situ hybridization (FISH) test (peptide nucleic acid [PNA]-FISH) that distinguished S. aureus from coagulase-negative staphylococci (4).…”
Section: Discussionmentioning
confidence: 99%
“…obtaining an echocardiograph (69,81,83,85,87,88), (iii) removing infected foci (80,86,89), (iv) providing a longer duration of treatment for complicated SAB (80)(81)(82)(83)(84)(86)(87)(88)(89), and (v) administering ␤-lactam antibiotics for MSSA infections (80,81,83,86,88,89). Eleven studies also reported that ID consultation for SAB is associated with reduced patient mortality rates (61, 62, 80-85, 87, 88, 90).…”
Section: Outcomes and Managementmentioning
confidence: 99%
“…An infectious diseases (ID) consultation can play a key role in facilitating the process of appropriate investigation and management of patients with SAB. ID consultation for patients with SAB is associated with higher rates of various quality-of-care metrics, including (i) obtaining follow-up blood cultures to assess the clearance of SAB (80)(81)(82)(83)(84)(85)(86), (ii) a The mean percentages of patients for each primary focus of infection from all the studies were as follows: 5% for infective endocarditis, 8% for osteoarticular, 19% for SSTI, 9% for pleuropulmonary, 26% for line related, 24% for no focus/unknown, and 11% for other foci. MRSA, methicillin-resistant S. aureus; HCA, health care associated; SSTI, skin and soft tissue infection.…”
Section: Outcomes and Managementmentioning
confidence: 99%
“…Las bacteriemias por Staphilococcus aureus representan el 7% de la cohorte, y la resistencia a meticilina es menor en nuestra área a lo descrito por otros autores, pero, en general, es en las bacteriemias por estos grampositivos donde múltiples trabajos [16][17][18] han evaluado la relevancia de la valoración clínica por un consultor en Patología Infecciosa. En nuestro estudio, y dado el pequeño tamaño de esta población, no se analizó concretamente este aspecto o subgrupo de bacteriemias.…”
Section: Asociación Colombiana De Infectologíaunclassified